Successfully Marketing a Collegiate Baseball Program Within Resource Constraints: A Special Case of Volunteerism - Tony Lachowetz; Sam Todd; Wendy Dees (Journal of Applied Sports Management, 2009)
Given resource constraints in marketing budgets of athletic departments, many marketers of intercollegiate athletics often face a difficult choice between marketing all sports fairly, and marketing only those sports that would provide the highest return on investment of marketing dollars. This case study explains the creative efforts made at one university to incorporate student volunteers when marketing, promoting, and selling tickets to collegiate baseball. After a brief overview of volunteerism in sport, this specific case first outlines the background to the problem, then details of how two student groups collectively contributed to stimulate the marketing efforts of the baseball program at Georgia Southern University (GSU).
Keywords: volunteering; sport industry; sport management students; marketing collegiate baseball; innovation; volunteers